LEKSIKON BAHASA KAILI SEBAGAI CERMINAN KEANEKARAGAMAN HAYATI DAN NONHAYATI DAERAH SULAWESI TENGAH - Deni Karsana (Balai Bahasa Sulawesi Tengah, 2014)
AbstractRevealing potential prosperity of a region through language, especially in lexicon, is urgentlyneeded. By doing this, it can be acknowledged that a certain region has natural source or has thehuman resources in processing those sources. A language can describe the potential prosperity of aregion. It is described from its vocabulary. An ethnic would be formulated by the lexicon masteringwhen it is applied in certain situation. This formula has been applied into the ethnic of Kaili whobecome the biggest ethnic in central of Sulawesi. The method which is applied in this paper isqualitative descriptive. The result shows that there are lexicons in Kaili language which havereflected the power of its society and the prosperity Central of Sulawesi. A wealth of biodiversity nonbiodiversity that mirror in Lexicon Kaili are mine, farm, plantation, gain of forest, and fishery. AbstrakPotensi kekayaan suatu daerah melalui bahasa, khususnya leksikon, sangat perlu diungkap.Dengan begitu, dapat diketahui suatu daerah tertentu memiliki kekayaan alam atau kemampuanmengolah hasil alam secara tepat. Hal ini tercermin dari penggunaan kosakatanya. Sebuah etnik akanterpolakan dari penguasaan leksikon yang digunakan dalam hal tertentu. Hal itu akan diungkap padaleksikon BK. Metode yang digunakan dalam tulisan ini adalah deskriptif kualitatif. Hasil pembahasanmenunjukkan bahwa leksikon-leksikon dalam bahasa mencerminkan kekayaan hayati dan nonhayatiSulawesi Tengah. Keaneragaman hayati dan nonhayati yang tercermin dalam leksikon BK adalahkeanekaragaman tambang, pertanian, perkebunan, hasil hutan, peternakan, dan perikanan.